PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN DENGAN METODE FRAUDTRIANGLE DAN SAS NO. 99 - Suryadi, Ari; Rasuli, M.; Indrawati, Novita (Jurnal Ekonomi, 2017)
This research aims to obtain empirical evidence of the effectiveness of the fraud triangle in detecting fraudulent financial statement. The variables of fraud triangle are used a proxy financial stability with GPM, SCHANGE, ACHANGE, CATA, SALAR, SALTA and INVSAL. External pressure that proxy by LEV, FINANCE, and FREEC. Personal financial need that proxy by OSHIP, and 5% OWN. Financial target that proxy by ROA. Nature of industry that proxy by RECEIVABLE, INVENTORY and FOPS. Ineffective monitoring that proxy by BDOUT, AUDCOMM, AUDCSIZE, IND and EXPERT. Organizational structure that proxy by CEO and TOTAL TURN. Rationalization that proxy by AUDCHANGE, AUDREPORT, and TACC then quality audit.The population of this research is the property and real estate companies listed on Indonesia Stock Exchange in 2011-2015 is 49 companies. Total samples of this research are 13 property and real estate companies used purposive sampling method. Statistical data analysis method used is logistic regression.The result of this research indicate that the financial stability that proxy by ACHANGE and SALTA, external pressure that proxy by LEV has significant on fraudulent financial statement. Meanwhile, the financial target that proxy by ROA and ineffective monitoring that proxy by AUDCOMM has no signifanct on fraudulent financial statement.